An Empirical Investigation of Women Small Business Owner - Tibbits, GE.; Kandasaami, T. (The International Journal of Accounting and Business Society, 1995)
Most of the studies in the existing literature are studies done in the United State, a few in U.K.  and very  less from  developing countries.  Women are starting business at a rate nearly four times that of men in U.S.  (Kaplan, 1988) and three times that of men both in Australia (ABS, 1991). and in Canada (Belcourt,  1990). Australia has got 692,700 small businesses which from 96.3% of a number of total businesses (ABS, 1990). In Australia, though women business owners are more than one  third  of the  total  small  business  owners,  research  on  female  entrepreneurs  is still in its infancy.